Using Concordance Software to Generate Academic Words in Applied Linguistics - Weningtyas Parama Iswari; Bibit Suhatmady; Yuni Utami Asih; Ida Wardani; Adrianto Ramadhan; Dynda Anastasya (Educational Studies: Conference Series, 2021)
Academic words include words that are not commonly encountered in formal circumstances and specific to particular fields of study. Undergraduate students of the English Department are required to acquire academic words in applied linguistics for academic reading and writing research articles. This paper reports on generating the academic word list for the students of the English Department by using AntConc, a concordance software application. In this study, corpus linguistic research was adopted, in particular the corpus-based analysis category. Data were gathered from approximately one thousand credible Applied Linguistics journal articles published from 2008 to 2021. AntConc software played a significant role in processing these data to get the intended corpus, which was then classified and categorized based on the frequency of occurrences. The results include an academic word list and its word family. These clusters of academic words are intended for undergraduate students of the English Department in the first up to fourth academic semesters to prepare them to participate in international academic discourse, such as writing and publishing research articles. This list can also be used as a basis for further research related to academic vocabulary. Academic words include words that are not commonly encountered in formal circumstances and specific to particular fields of study. Undergraduate students of the English Department are required to acquire academic words in applied linguistics for academic reading and writing research articles. This paper reports on generating the academic word list for the students of the English Department by using AntConc, a concordance software application. In this study, corpus linguistic research was adopted, in particular the corpus-based analysis category. Data were gathered from approximately one thousand credible Applied Linguistics journal articles published from 2008 to 2021. AntConc software played a significant role in processing these data to get the intended corpus, which was then classified and categorized based on the frequency of occurrences. The results include an academic word list and its word family. These clusters of academic words are intended for undergraduate students of the English Department in the first up to fourth academic semesters to prepare them to participate in international academic discourse, such as writing and publishing research articles. This list can also be used as a basis for further research related to academic vocabulary.